“Tantangan Penerapan Media Interaktif dalam Pembelajaran IPA Berbasis SETS: Studi Persepsi Siswa SMP” (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2025)
Science learning in the digital era requires innovation to ensure that students not only understand concepts but are also able to connect them with real-life contexts. This study aims to analyze the challenges of implementing interactive media in Science learning based on the Science, Environment, Technology, and Society (SETS) approach at the junior high school level. The research employed a mixed-methods approach with a case study design involving 30 students and 3 science teachers. Data were collected through student perception questionnaires and teacher interview sheets. The questionnaire results showed an average perception score of 3.97 out of 5, indicating a positive response toward the integration of interactive media and the SETS approach. However, further analysis revealed that although interactive media enhanced students’ understanding and motivation, their activeness, self-confidence, and ability to connect science with technology and social issues still need improvement. These findings indicate that the main challenge in implementing interactive media based on the SETS approach lies in strengthening students’ participation and scientific communication through more collaborative and contextual learning activities.